Вы находитесь на странице: 1из 3

(A) Identifying quadratic expression

1. A quadratic expression is an algebraic expression of the form

ax2 + bx +c,

where a, b and c are constants, a 0 and x is an unknown.


(a) The highest power of x is 2.
(b) For example, 5x2 6x + 3 is a quadratic expression.
Example 1
State whether each of the following is a quadratic expression in one unknown.
(a) x2 5x + 3
(b) 8p2 + 10
(c) 5x + 6
(d) 2x2 + 4y + 14
(e) 2p+ 1 p +6
(f) y3 3y + 1
Solution:
(a) Yes. A quadratic expression in one unknown.
(b) Yes. A quadratic expression in one unknown.
(c) Not a quadratic expression in one unknown. The highest power of the unknown x
is not 2.
(d) Not a quadratic expression in one unknown. There are 2 unknowns, x and y in
the quadratic expression.
(e) Not a quadratic expression in one unknown. The highest power of the unknown x
is not 2.
1 p = p 1
(f) Not a quadratic expression in one unknown. The highest power of the unknown x
is not 2.
2. A quadratic expression can be formed by multiplying two linear expressions.
(2x + 3)(x - 3) = 2x2 3x 9

Example 2
Multiply the following pairs of linear expressions.
(a) (4x + 3)(x 2)
(b) (y 6)2
(c) 2x (x 5)
Solution:
(a) (4x + 3)(x 2)
= (4x)(x) + (4x)(-2) +(3)(x) + (3)(-2)
= 4x2 8x + 3x 6
= 4x2 5x 6

(b) (y 6)2
= (y 6)(y 6)
= (y)(y) + (y)(-6) + (-6)(y) + (-6)(-6)
= y2 -6y 6y + 36
= y2 - 12y + 36

(c) 2x (x 5)
= 2x(x) + 2x(-5)
= 2x2 10x
Example 1:
Form a quadratic expression by multiplying each of the following.
(a) (6p 2)(2p 1)
(b) (m + 5)(4 7m)
(c) (x + 2) (2x 3)

Solution:
(a) (6p 2)(2p 1)
= (6p)(2p) + (6p)(-1) + (-2)(2p) +(-2)(-1)
= 12p2 6p 4p + 2
= 12p2 10p + 2
(b) (m + 5)(4 7m)
= (m)(4) + (m)(-7m) + (5)(4) + (5)(-7m)

= 4m 7m2 + 20 35m
= 7m2 31m + 20

(c) (x + 2) (2x 3)
= (x)(2x) + (x)(-3) + (2)(2x) + (2)(-3)
= 2x2 -3x + 4x 6
= 2x2 + x - 6